Variation of growth ring width in maritime pine (Pinus pinaster Ait.) - Anjos, O. (2013)
The aim of this study was to incorporate ring width data into sawing yield strudies through simulation and tree modelling techniques. Results on data analysis measuring anual growth variation contribute also to the raw material characterisation.